Beyond the “Grammar” - Vesna Main (Revue LISA)
With specific reference to Moo Pak, the article examines the poetics of Gabriel Josipovici’s fiction and argues that his opus centres on questions of art and creativity in a world where oracles no longer speak to us. Many of the protagonists of his short stories and novels are artists or writers, suffering from the anxiety that is brought about by the compelling need to create and the accompanying awareness of the necessity of failure. With its emphasis on hermeneutic impossibility and ontological uncertainty, Josipovici’s narrative grammar does not conform to the dominant trend of social realism in the contemporary British novel, a genre that differs little from its predecessor of a century ago. Rather, Josipovici writes in the European tradition of modernism. The article questions his marginalisation by the literary establishment, and argues that it should be the role of the critic to help the readers break away from the homogeneity of the contemporary British novel and become more receptive to other types of texts, those that are written beyond the grammar of dominant trends.